Diabetic Cardiomyopathy: Intersection of Macrovascular and Microvascular Disease, or Much More? - Mitevska, Irena; Bosevski, Marijan (Македонско лекарско друштво = Macedonian Medical Association, 2016)
Cardiovascular disease is responsible for over 75% of deaths in diabetic patients, the majority caused by coronary artery disease (CAD) and heart failure. Cardiovascular morbidity and mortality in diabetic patients might be independently associated with other pathophysiologic mechanisms than coronary artery disease, epicardial and microvascular disease. There is an increasing notion that diabetic patients suffer from an additional cardiac condition named “diabetic cardiomyopathy”. There are several clinical, experimental, pathological and epidemiological researches that support the existence of a specific “diabetic cardiomyopathy”. This is assumed to be influenced by complex interaction of several metabolic changes that leads to both functional and structural alterations of the diabetic myocardium. In this review epidemiological aspects and clinical implications of this condition are presented.